Seasonal variations and spatial distribution of particulate matter emissions from a ventilated laying hen house in Northeast China - Guo, Li; Zhao, Dongsen; Zhao, Bo; Ma, Shuli; Liu, Xiaolin; Li, Mo; Liu, Xin (International Journal of Agricultural and Biological Engineering, 2020)
With the development of concentrated animal feeding operations in China, the air pollution problem has drawn widespread public attention. Residents living near farms are suffering from the emissions of particulate matter (PM) and odors. However, scientific data on the characteristics of these emissions are limited to the establishment and evaluation of mitigation strategies in China. This study was conducted to provide fundamental information on the concentrations of PM inside and outside a typical ventilated laying hen house in northeastern China. The results showed that outdoor PM concentrations of this laying hen house did not meet the requirements of the environmental quality standard of China’s livestock and poultry farms in the two days out of six sampling days in summer, while indoor PM concentrations met the environmental requirements during this study. The indoor and outdoor PM concentrations were highly correlated in summer, and over 60% of particles indoor were emitted outside via mechanical ventilation. There were more fine particles dominated both inside and outside of the laying hen house. Besides, twelve and nine elements were measured from the PM sources inside and outside laying hen house, respectively. PM control strategies may be adjusted based on the status of exhaust fans, the ages of laying hens, atmospheric conditions, and routine house management to well reduce PM emissions and improve control efficiency.Keywords: particulate matter, ventilated laying hen house, air emission, animal feeding operationDOI: 10.25165/j.ijabe.20201303.5111Citation: Guo L, Zhao D S, Zhao B, Ma S L, Liu X L, Li M, et al. Seasonal variations and spatial distribution of particulate matter emissions from a ventilated laying hen house in Northeast China. Int J Agric & Biol Eng, 2020; 13(3): 57–63.